Electric properties of Mn-substituted Na0.5Bi0.5TiO3 ceramics in unpoled and poled states. (1st December 2020) - Suchanicz, J.; Wąs, M.; Nowakowska-Malczyk, M.; Handke, B.; Bik, M.; Konieczny, K.; Czaja, P.; Kluczewska-Chmielarz, K.; Sitko, D.; Stanuch, K.; Sokolowski, M.
ABSTRACT: The Mn-substituted NBT ceramics were prepared by the conventional ceramic fabrication technique. X-ray diffraction (XRD) studies indicated the formation of perovskite phase with rhombohedral symmetry and with small amount of second phase. It was found that 0.5mol% and 0.1mol% dopant concentration enhances piezoelectric coefficients of d33 and k33, increases the depolarization temperature Td and decreases the dielectric loss. Dielectric study showed the existence of a diffuse phase transition at Tm  ≈ 320°C. It was shown that a prior electric field poling process changes the character of ϵ ( T ) and tan δ ( T ) functions, as well as shifts of Td and Tm to higher temperature. The effects are mainly caused by the reinforcement of polarization/domain ordering and by the change of content rhombohedral/tetragonal phases by electric field action. The results were discussed in terms of lattice distortion and change of defect concentration.